Ecological and dynamic analysis of gut microbiota in the early stage of azomethane-dextran sodium sulfate model in mice - Sun, Ruizheng; Chen, Hao; Yao, Siqi; Yu, Zheng; Lai, Chen; Huang, Jing (Frontiers in Cellular and Infection Microbiology, 2023)
The success rate of azomethane-dextran sodium sulfate (AOM-DSS) model in mice has been a long-standing problem. Treatment of AOM and the first round DSS induces acute colitis and is of great significance for the success of AOM-DSS model. In this study, we focused on the role of gut microbiota in the early stage of AOM-DSS model. Few mice with obvious weight loss and high disease-activity score survived from double strike of AOM and the first round DSS. Different ecological dynamics of gut microbiota were observed in AOM-DSS treated mice. Pseudescherichia, Turicibacter, and Clostridium_XVIII were of significance in the model, uncontrolled proliferation of which accompanied with rapid deterioration and death of mice. Akkermansia and Ruthenibacterium were significantly enriched in the alive AOM-DSS treated mice. Decrease of Ligilactobacillus, Lactobacillus, and Limosilactobacillus were observed in AOM-DSS model, but significant drop of these genera could be lethal. Millionella was the only hub genus of gut microbiota network in dead mice, which indicated dysbiosis of the intestinal flora ecology and fragility of microbial network. Our results will provide a better understanding for the role of gut microbiota in early stage of AOM-DSS model and lay the foundation for improving the success rate of model construction.